Merekonstruksi Literasi Ekologi: Tantangan dan Peluang bagi Kalangan Mahasiswa Calon Guru Biologi - Yan Piter Basman Ziraluo (Jurnal Pendidikan Biologi Undiksha, 2025)
This study aims to reconstruct the concept of ecological literacy to make it relevant to technological developments, the dynamics of global environmental change, and the need for sustainable education in the modern era. This study was conducted using a descriptive-qualitative method through content analysis of various scientific articles indexed by Scopus that were published from 2020 to 2025. Data were collected through a systematic literature review technique with source selection based on credibility and thematic relevance, and then analyzed thematically to identify patterns of integration, challenges, and opportunities for strengthening ecological literacy. A total of 27 articles were analyzed, describing the answers to the research questions and objectives of this study. The results of the study show that ecological literacy can be strengthened through cross-disciplinary integration, the application of green technology in learning, and the support of sustainable campus policies. Significant findings confirm that ecological literacy not only covers conceptual knowledge, but also shapes transformative competencies that encourage behavioral change and active participation in maintaining environmental balance.